2012
DOI: 10.1016/j.ajhg.2011.11.016
|View full text |Cite
|
Sign up to set email alerts
|

De Novo and Inherited Mutations in COL4A2, Encoding the Type IV Collagen α2 Chain Cause Porencephaly

Abstract: Porencephaly is a neurological disorder characterized by fluid-filled cysts or cavities in the brain that often cause hemiplegia. It has been suggested that porencephalic cavities result from focal cerebral degeneration involving hemorrhages. De novo or inherited heterozygous mutations in COL4A1, which encodes the type IV α1 collagen chain that is essential for structural integrity for vascular basement membranes, have been reported in individuals with porencephaly. Most mutations occurred at conserved Gly res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 18 publications
0
65
0
1
Order By: Relevance
“…For this, a PubMed search was performed, identifying 27 articles with clinical and mutation data on COL4A1 7,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][29][30][31][32][33][34][35][36][37][38][39][40] and 3 articles with data on COL4A2 mutations. [26][27][28] A total of 137 individuals with a COL4A1 mutation from 60 families and 15 individuals with a COL4A2 mutation from 7 families have been reported. Several clinical phenotypes were identified and described in more detail.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, a PubMed search was performed, identifying 27 articles with clinical and mutation data on COL4A1 7,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][29][30][31][32][33][34][35][36][37][38][39][40] and 3 articles with data on COL4A2 mutations. [26][27][28] A total of 137 individuals with a COL4A1 mutation from 60 families and 15 individuals with a COL4A2 mutation from 7 families have been reported. Several clinical phenotypes were identified and described in more detail.…”
Section: Methodsmentioning
confidence: 99%
“…In 2012 several parallel genetic, epidemiologic, and functional studies revealed COL4A2 mutations in both familial and sporadic porencephaly. [26][27][28] The disease resulting from both COL4A1 and COL4A2 mutations is extremely variable, with broad intra-and interfamilial variation and evidence for reduced penetrance. Sporadic individuals with severe presentation may harbor a de novo mutation.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of diseases not expected to be diagnosed early in life or with variable phenotypic presentations needs to be considered. An example of this kind of disease may be the disorder caused by mutations in COL4A1/COL4A2, which is associated with white matter anomalies and periventricular cysts, but can remain asymptomatic until late in life [15] . Since the number of familial cases with PVPC diagnosed in utero is small and we have not been able to diagnose a genetic etiology, at present we are not able to exclude a possible coincidental occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, deletions of COL4A1 were first shown to cause porencephaly, cerebral hemorrhage, and microangiopathy in humans (Rodahl et al, 2013). Heterozygous mutations of COL4A2 have been associated with porencephaly 2 (OMIM 614483) (Yoneda et al, 2012) and increased nuchal translucency (Jeanne et al, 2012;Weng et al, 2012). Haploinsufficiency of COL4A1 and COL4A2 may be associated with susceptibility to intracerebral hemorrhage (OMIM 614519) (Jeanne et al, 2012;Weng et al, 2012) and increased nuchal translucency .…”
Section: Discussionmentioning
confidence: 99%